INTELLIGENT NAVIGATION FOR AUTONOMOUS MOBILE ROBOT - ROSLI, NAJUA (IRC, 2019)
Autonomous mobile robot (AMR) has a vast application in industry generally in logistics. It is an attempt made by most manufacturing companies such as Finisar Malaysia Sdn. Bhd. to catch up with the digital trend in the fourth industrial revolution or known as industry 4.0. Intelligent navigation system is crucial to build a mobile robot that can move autonomously in any environment. An AMR kit known as TurtleBot3 Burger is used in this project to demonstrate the intelligent navigation system based on Robot Operating System (ROS) platform. SLAM is a practical method for mobile robot especially when it is implemented in a dynamic surrounding. The laser distance sensor (LDS) mounted on TurtleBot3 Burger is using laser light to detect obstacles in its surrounding for localization and mapping. This intelligent navigation system is developed to be navigated autonomously indoor. Therefore, this project is tested in enclosed space in UTP such as hostel room to resemble a production line with dynamic environment.